Peripheral Cemento-Ossifying Fibroma: Case Series Literature Review - Kiran Kumar Ganji; ArunKumar Bhimashankar Chakki; Sharanbasappa Chandrashekar Nagaral; Esha Verma (Case Reports in Dentistry)
The concept of fibroosseous lesions of bone has evolved over the last several decades and now includes two major entities: fibrous dysplasia and ossifying fibroma. Peripheral cemento-ossifying fibroma is a relatively rare tumour classified between fibroosseous lesions. It predominantly affects adolescents and young adults, with peak prevalence between 10 and 19 yrs. The cemento-ossifying fibroma is a central neoplasm of bone as well as periodontium which has caused considerable controversy because of confusion regarding terminology and the criteria for its diagnosis. The cemento-ossifying fibroma is odontogenic in origin, whereas ossifying fibroma is of bony origin. Lesions histologically similar to peripheral ossifying fibroma have been given various names in existing literature. Therefore, we present and discuss in this paper a series of cases of peripheral cemento-ossifying fibroma emphasizing the differential diagnosis.